1987
DOI: 10.1007/bf00424810
|View full text |Cite
|
Sign up to set email alerts
|

Perceived exertion related to heart rate and blood lactate during arm and leg exercise

Abstract: To compare some psychophysiological responses to arm exercise with those to leg exercise, an experiment was carried out on electronically braked bicycle ergometers, one being adapted for arm exercise. Eight healthy males took part in the experiment with stepwise increases in exercise intensity every 4 min: 40-70-100-150-200 W in cycling and 20-35-50-70-100 W in arm cranking. Towards the end of each 4 min period, ratings of perceived exertion were obtained on the RPE scale and on a new category ratio (CR) scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
329
1
17

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(354 citation statements)
references
References 19 publications
7
329
1
17
Order By: Relevance
“…As such, we interpret the present data as supporting the validity of the Session RPE method as an alternative method of monitoring exercise training. The present data are comparable with previous studies 2,3,19,20,22 which have shown RPE to be a valid and reliable measure of momentary exercise intensity. We chose not to measure blood lactate responses during either incremental or constant intensity exercise, which is the other widely accepted objective method of measuring exercise intensity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As such, we interpret the present data as supporting the validity of the Session RPE method as an alternative method of monitoring exercise training. The present data are comparable with previous studies 2,3,19,20,22 which have shown RPE to be a valid and reliable measure of momentary exercise intensity. We chose not to measure blood lactate responses during either incremental or constant intensity exercise, which is the other widely accepted objective method of measuring exercise intensity.…”
Section: Discussionsupporting
confidence: 92%
“…2,3,19,20,22 At that time, limited objective data were presented in support of the validity of the technique, on the basis of both heart rate (HR) and blood lactate responses. In the subsequent decade, several papers have used the Session RPE method in a variety of settings and have demonstrated its value relative to quantifying exercise training intensities 4,7,8,9,16,17,23 and as the intensity component of larger schemes of evaluating training programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the maximum heart rates observed in the exercise test, the target zone was calculated at between 60 and 80% of the maximum heart rate for aerobic exercises. For exercise intensity control, the Borg rating of perceived exertion scale 13 was used in addition to the target heart rate and the patients were advised to exercise with mild to moderate intensity, corresponding to levels 11 to 13 of the scale, so that they would remain only mildly breathless. The aerobic component of the physical conditioning sessions was supplemented by warm-up, stretching and cool-down activities.…”
Section: Methodsmentioning
confidence: 99%
“…Alterações da musculatura esquelética incluem acúmulo de lactato em cargas baixas, redução do tamanho mitocondrial e capacidade oxidativa, atrofia de fibras tipo I, apoptose e respostas metabólicas inapropriadas 613 . Nesses pacientes, o treinamento físico aumenta a capacidade funcional máxima e submáxima, e a magnitude deste aumento é similar e adicional àquela obtida com terapia farmacológica.…”
Section: -Reabilitação Em Populações Especiaisunclassified